2009
DOI: 10.1016/j.jacc.2009.03.037
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Heart Failure With Normal Ejection Fraction

Abstract: In HFNEF there are widespread abnormalities of both systolic and diastolic function that become more apparent on exercise. HFNEF is not an isolated disorder of diastole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 436 publications
(102 citation statements)
references
References 52 publications
(58 reference statements)
2
99
0
1
Order By: Relevance
“…Previous studies showed that CFR is impaired in hypertrophic cardiomyopathy,12 HF,18 and dilated cardiomyopathy 16. In HFpEF patients, a subtle abnormality of resting myocardial function becomes apparent during the stress condition 19, 20, 21. Therefore, we hypothesized that CFR might be decreased in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies showed that CFR is impaired in hypertrophic cardiomyopathy,12 HF,18 and dilated cardiomyopathy 16. In HFpEF patients, a subtle abnormality of resting myocardial function becomes apparent during the stress condition 19, 20, 21. Therefore, we hypothesized that CFR might be decreased in patients with HFpEF.…”
Section: Introductionmentioning
confidence: 94%
“…Tan, et al 170 combined traditional and newer echocardiographic parameters in their examination of patients at rest and during aerobic exercise. They proposed that in HFNEF, both systolic and diastolic abnormalities cause exercise limitation, particularly involving ventricular twist, delayed untwisting and deformation (strain).…”
Section: Diastolic Stress Testmentioning
confidence: 99%
“…17 Although both the subendocardial and the subepicardial longitudinal fibers contribute to longitudinal deformation, in the normal heart, they counterbalance each other's ability to produce circumferential deformation. The subendocardial fibers seem more susceptible to dysfunction 10,18 than the mid and epicardial fibers. This impairment of the subendocardial longitudinal fibers also leads to attenuated subendocardial right-handed helix fiber shortening during systole, potentially resulting in a failure to fully counterbalance the subepicardial left-handed helix fiber shortening and resulting in increased circumferential deformation.…”
mentioning
confidence: 94%